1995
DOI: 10.1002/path.1711770304
|View full text |Cite
|
Sign up to set email alerts
|

In situ detection of Epstein–Barr virus in non‐small cell lung carcinomas

Abstract: Epstein-Barr virus (EBV) is strongly associated with nasopharyngeal carcinoma and lymphoepithelioma-like carcinomas (LELC) of foregut-derived organs. Recently this group of EBV-associated carcinomas has been expanded by the identification of the virus in conventional adenocarcinomas of the stomach. In situ hybridization (ISH) using a sensitive digoxigenin-labelled EBER RNA probe was performed on 167 consecutive unselected primary non-small cell lung carcinomas, to determine the frequency of EBV association in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 28 publications
2
67
0
Order By: Relevance
“…13,12 However, the neoplastic cells had an extremely low 7 LMP1 expression, and in situ hybridization for EBV early RNA (EBER) and clonal episomal EBV sequences have been demonstrated in tumour tissue, but only in Asian 9,23,12,25,26 and in two caucasic patients. 18,19 We agree with these data because our five cases of pure lymphoepitheliomalike carcinomas have been negative for EBV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,12 However, the neoplastic cells had an extremely low 7 LMP1 expression, and in situ hybridization for EBV early RNA (EBER) and clonal episomal EBV sequences have been demonstrated in tumour tissue, but only in Asian 9,23,12,25,26 and in two caucasic patients. 18,19 We agree with these data because our five cases of pure lymphoepitheliomalike carcinomas have been negative for EBV.…”
Section: Discussionmentioning
confidence: 99%
“…A PCR-ELISA technique for human herpesvirus family detection was performed (Herplex t Genomica, SAU, Madrid, Spain) according to manufacturer's instructions. 20 Briefly, we extracted DNA from the microdissected 5-mm sections from paraffin blocks, and a PCR-ELISA 25 9 Lymphoepitelioma like 100% EBER, 44% LMP1, 0% EBNA2 158 NSCLCs 0% EBER +++ China 6 11 Lymphoepitelioma like 100% EBER +++ USA 12 80 Adenocarcinomas 0% EBER1 50 Mesotheliomas 0% EBER1 Japan 17 1 procedure was performed. The PCR mix contained primers against a 194 bp sequence of DNA viral polymerase from herpes simplex types 1 and 2, varicella zoster, cytomegalovirus, EBV and human herpesvirus 6.…”
Section: Molecular Analysis For Viral Sequencesmentioning
confidence: 99%
“…Several studies have demonstrated Epstein-Barr virus genome in pulmonary carcinomas with morphologic features of lymphoepithelioma-like carcinoma in Asian pattents [8][9][10][11] and Western populations. 12 We studied Epstein-Barr virus RNA in 78 cases of pulmonary nonlymphoepitheliomalike carcinoma using in situ hybridization methodology in 1992, and found none of them to be positive for Epstein-Barr virus.…”
Section: Discussionmentioning
confidence: 99%
“…7 Pulmonary carcinomas with morphologic features of lymphoepithelioma-like carcinoma have also been reported to harbor Epstein-Barr virus. [8][9][10][11] Most of these reports of Epstein-Barr virus-associated epithelial malignancies were in Asian patients. In contrast, there are few reports demonstrating EpsteinBarr virus infection in pulmonary carcinoma in Western populations.…”
mentioning
confidence: 99%
“…Additionally, EBV has also been reported with gastric cancer (Koriyama et al, 2001;Takada, 2000), breast (Labrecque et al, 1995;Bonnet et al, 1999;Fina et al, 2001) and lung cancer (Castro et al, 2001;Han et al, 2001; M.P. Wong et al, 1995). For colorectal cancer, although early studies have detected high rates of EBV infection in colorectal carcinoma tissue, using PCR, immunohistochemisrty and fluorescence in situ hybridization (Song et al, 2006;Liu et al, 2002Liu et al, , 2003, only one study reported significant difference in EBV detection rates between colorectal carcinoma tissue and adjacent normal mucosa (Song et al, 2006).…”
Section: Other Virusesmentioning
confidence: 94%